(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present study Computer supported drug design technique for the development processes additionally we feature the Overview of QSAR and virtual screening work process. Also the postulation is a general dialog on crafted by the proposition and a proposition on how all can be coordinated inside the drug disigning and development pipeline.